2009
DOI: 10.1007/s00213-009-1678-1
|View full text |Cite
|
Sign up to set email alerts
|

Social experiences affect reinstatement of cocaine-induced place preference in mice

Abstract: Social experiences modify vulnerability to reinstatement, acting as prevention or risk factors in the development of drug addiction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 56 publications
6
43
0
Order By: Relevance
“…If this is the case, adolescent mice are likely to be less responsive to cocaine. In accordance with this hypothesis, we have previously observed that adolescent mice living in crowded conditions do not present reinstatement after a cocaine priming, while adult mice housed in the same conditions show a significantly increased response to cocaine (Ribeiro do Couto et al, 2009). The fact that most playful attacks in adolescent mice elicited defensive reactions limited to evasion undermines this argument; in the present study, socially defeated adolescent mice displayed submissive behavior similar to that observed in adults (Pellis and Pasztor, 1999).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…If this is the case, adolescent mice are likely to be less responsive to cocaine. In accordance with this hypothesis, we have previously observed that adolescent mice living in crowded conditions do not present reinstatement after a cocaine priming, while adult mice housed in the same conditions show a significantly increased response to cocaine (Ribeiro do Couto et al, 2009). The fact that most playful attacks in adolescent mice elicited defensive reactions limited to evasion undermines this argument; in the present study, socially defeated adolescent mice displayed submissive behavior similar to that observed in adults (Pellis and Pasztor, 1999).…”
Section: Discussionsupporting
confidence: 89%
“…In accordance with the results reported herein, adult mice exposed to social defeat stress (using the intruderresident model) have been shown to exhibit significantly stronger CPP for the cocaine-paired chamber than unstressed mice (McLaughlin et al, 2006). Furthermore, social defeat during an agonistic encounter in a neutral area prior to a reinstatement test has been shown to reinstate cocaine CPP in adult mice (Land et al, 2009;Titomanlio et al, 2013) and to increase susceptibility to cocaine-induced reinstatement of CPP (Ribeiro Do Couto et al, 2009). These results are in line with those of numerous studies which have demonstrated that social defeat increases vulnerability to cocaine self-administration (Haney et al, 1995;Miczek and Mutschler, 1996;Tidey and Miczek, 1997;Miczek, 2001, 2005;Yap and Miczek, 2007;Covington et al, 2008;Quadros and Miczek, 2009;Boyson et al, 2011;Cruz et al, 2011).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The only study to examine social housing effects outside of the cocaine self-administration context in adults found no effect during acquisition or maintenance (Bozarth et al 1989). Also, no effects on morphine-, heroin-, or cocaine-CPP have been observed across isolated and social-housed adult rodents (Herzig and Schmidt 2005; Ribeiro Do Couto et al 2009; Schenk et al 1985). …”
Section: Social Experiences Proximal In Time To the Drug Experience Bmentioning
confidence: 97%
“…Indeed, acute exposure to social defeat stress produces reinstatement of previously-extinguished place preference to cocaine or morphine in mice (21, 34). However, previous attempts by us and others to reinstate previously-extinguished operant self-administration using acute social defeat stress have been unsuccessful (our unpublished data; 35).…”
Section: Discussionmentioning
confidence: 99%